Impact of natural disasters on the income distribution - Regina Pleninger (ETH Zurich, KOF Swiss Economic Institute, 2020)
During the last decades, the United States experienced an increase in the number of natural disasters as well as their destructive capability. Several studies suggest a damaging effect of natural disasters on income. In this paper, I estimate the effects of natural disasters on the entire income distribution using county-level data in the United States. In particular, I determine the income fractions that are affected by natural disasters. The results suggest that natural disasters primarily affect middle incomes, thereby leaving income inequality levels mostly unchanged. In addition, the paper examines potential channels that intensify or mitigate the effects, such as social security or the severity of natural disasters. The findings show that social security, assistance programs and migration are important adaptation tools that reduce the effects of natural disasters. In contrast, the occurrence of multiple and severe disasters aggravate the effects.
hdl:20.500.11850/404238
Keywords: D63; O51; Q54; R23; 330; Disaster; Income Distribution; United States; Migration; Panel Data